Effects of the potential lithium-mimetic, ebselen, on brain neurochemistry: a magnetic resonance spectroscopy study at 7 tesla - Masaki, C; Sharpley, A; Godlewska, B; Berrington, A; Hashimoto, T; Singh, N; Vasudevan, S; Emir, U; Churchill, G; Cowen, P (Oxford University Press, 2016)
Introduction: Lithium remains the most effective treatment for bipolar disorder but tolerance and safety issues complicate its clinical use. The antioxidant drug, ebselen, has been proposed as a possible lithium-mimetic based on its ability in animals to inhibit inositol monophosphatase (IMPase) and lower brain inositol, actions which it shares with lithium. Objectives: The primary aim of the study was to determine whether treatment with ebselen lowered levels of inositol in the human brain. We also assessed the effect of ebselen treatment on other brain neurometabolites, including glutathione, glutamate, glutamine, and glutamate+glutamine (Glx). Methods: We studied 20 healthy volunteers who were tested on two occasions receiving either ebselen (3600mg over 24 hours) or identical placebo in a double-blind, random-order, cross-over design. Two hours after the final dose of ebselen/placebo, participants underwent proton magnetic resonance spectroscopy (1H MRS) at 7 tesla (7T) with voxels placed in anterior cingulate and occipital cortex (Figure 1). Neurometabolite levels were calculated using an unsuppressed water signal as a reference and corrected for individual cerebrospinal fluid content in the voxel. Results: Ebselen produced no effect on neurometabolite levels in the occipital cortex. In the anterior cingulate cortex, ebselen lowered concentrations of inositol as well as those of glutathione, glutamine, glutamate and Glx (Table 1). Conclusions: The study suggests that at the dosage used, ebselen produces a functional inhibition of IMPase in the human brain. The ability of ebselen to lower indices of glutamate activity are consistent with its action, reported in animal experimental work, to inhibit the enzyme, glutaminase. Ebselen appears to have potential as a repurposed treatment for bipolar disorder and it would be of interest to see if similar biochemical alterations are produced by ebselen treatment in this patient group.